Tajikistan’s agrifood system structure - Khakimov, Parviz; Diao, Xinshen; Goibov, Manuchehr; Ashurov, Timur (International Food Policy Research Institute, 2025)
Tajikistan’s agrifood system (AFS) accounted for 34.7 percent of Tajikistan’s national GDP and 58 percent of employment in 2022. Primary agriculture alone contributed one-quarter of total GDP and 54.9 percent of employment, while the four off-farm components of the AFS contributed about 10 percent of GDP and 3.2 percent of employment. The share of employment in primary agriculture in total employment in AFS (AgEmp+) is huge, 94 percent. The off-farm components of the AFS therefore accounted for close to 30 percent of AgGDP+ and only 5 percent of AgEMP+. Though Tajikistan is an agrarian economy, it imports a lot of foods, and the shares of imports in the country’s total merchandise imports are consistently high, around 22 percent between 2016 and 2022. For the same period, food exports as a percentage of total merchandise exports were just 3 percent (World Bank 2023). Agrifood imports also grew more rapidly, increasing by a multiple of 16 between 2000 and 2023, while exports only doubled over the same period (Khakimov, et al. 2024).